Legal Semiotics - Vladimir Valentinovich Kozhevnikov (Britain International for Academic Research (BIAR) Publisher, 2023)
The article reveals the concept of semiotics and the stages of its formation, as well as the semiotics of law; some concepts of semiotic-legal researches are analyzed; a forecast is given from the point of view of the application of semiotics of law in the future.